PENGARUH REKRUTMENT DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. CIBADAK INDAH SARI FARM CABANG CARINGIN - Fisga Pebrianika; Abdul Azis (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to determine the effect of recruitment and motivation on employee performance at PT. Cibadak Indah Sari Farm, Caringin Branch. The research method applied is a descriptive quantitative approach with data collection techniques through through observation, questionnaires, and literature studies. The research population consists of all employees of PT. Cibadak Indah Sari Farm, totalling 135 people with 101 employees selected using random sampling techniques. Data analysis with validity tests, reliability tests, t tests, F tests, and the coefficients of determination (R²). The results of this study indicate recruitment has a positive and significant effect on employee performance partially with a t-value of 2.813 > table t 1.984 and a significance level of 0.006 > 0.05. the motivation variable also has a positive and significant effect on employee performance with t value of 5.381 > t table 1.984 and a significance value of 0.000 < 0.05. Simultaneously, recruitment and motivation significantly influence employee performance at PT. Cibadak Indah Sari Farm as showed by F value of 102.901 > F table 3.09 with a significance of 0.000 < 0.05. The coefficient of determination shows an R-Square value of 0.677. This indicataed that 67% of the variation in employee performance is influenced by recruitment and motivation, while the remaining 33% is influenced by other factors not examined in this study.